About One Way to Increase the Accuracy of Navigation System for Ground Wheeled Robot Used in Aircraft Parking. Issue 4 (1st October 2020) - Chernomorsky, Alexander I.; Lelkov, Konstantin S.; Kuris, Eduard D.
ABSTRACT: The article discusses a ground-based wheeled robot (GWR), designed to operate at airfields, in particular at aircraft parking lots for the purpose of patrolling or photographing the lower part of the aircraft. The purpose of the article is to find a way to increase the accuracy of the navigation system for a ground wheeled robot used in aircraft parking. All initial and final calculations were performed in the navigation coordinate system (CS). Also, the starting CS (SCS) and CS associated with the GWR were used. A trajectory of detouring the aircraft landing gear racks was obtained, at which the influence of aircraft position errors at the airfield parking and scanning laser range finder (LIDAR) measurement errors on the accuracy of determining the location coordinates of the aircraft and GWR can be minimized. The influence of linear and angular errors of the aircraft position on the value of the error in determining the location of the GWR was studied. A correction structure was developed based on Kalman filter of GWR navigation system according to the calculated coordinates. The results of modeling the operation of integrated navigation system with the proposed correction channel were demonstrated, which have shown the effectiveness of the proposed correction method. Based on the analysis of the indicated GWR navigation systems, it can be concluded that the features of the use of additional sensors are determined by the purpose of GWR and, accordingly, the trajectory of its movement. The proposed correction algorithm for the navigation system based on LIDAR measurements based on the initial research is an adequate and effective alternative to using GPS in limited conditions.